2020
DOI: 10.3390/cells9091930
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Induces Epithelial to Mesenchymal Transition of Human Glioblastoma Cells

Abstract: The mesenchymal phenotype of glioblastoma multiforme (GBM), the most frequent and malignant brain tumor, is associated with the worst prognosis. The epithelial–mesenchymal transition (EMT) is a cell plasticity mechanism involved in GBM malignancy. In this study, we determined 17β-estradiol (E2)-induced EMT by changes in cell morphology, expression of EMT markers, and cell migration and invasion assays in human GBM-derived cell lines. E2 (10 nM) modified the shape and size of GBM cells due to a reorganization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 121 publications
(135 reference statements)
4
48
0
Order By: Relevance
“…EMT is activated by several signaling pathways that can cooperate in a cell-type-specific and context-dependent manner to activate the expression of EMT-inducing transcription factors (EMT-TFs), which coordinate epithelial gene repression and mesenchymal gene induction [ 21 ]. Some signaling pathways that activate the EMT-TFs in GBM include those mediated by transforming growth factor β (TGF-β) [ 22 ], receptor tyrosine-kinases (RTKs) [ 23 , 24 , 25 ], wingless-integration (Wnt)/beta-catenin [ 26 , 27 ], hypoxia [ 28 , 29 ], inflammatory cytokines such as interleukin 6 (IL-6) [ 30 ], and steroid hormones such as 17β-estradiol (E2) [ 31 ]. The complexity of the molecular network and the variables in each cell system provoke a partial or intermediate EMT program, resulting in very diverse cellular phenotypes [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT is activated by several signaling pathways that can cooperate in a cell-type-specific and context-dependent manner to activate the expression of EMT-inducing transcription factors (EMT-TFs), which coordinate epithelial gene repression and mesenchymal gene induction [ 21 ]. Some signaling pathways that activate the EMT-TFs in GBM include those mediated by transforming growth factor β (TGF-β) [ 22 ], receptor tyrosine-kinases (RTKs) [ 23 , 24 , 25 ], wingless-integration (Wnt)/beta-catenin [ 26 , 27 ], hypoxia [ 28 , 29 ], inflammatory cytokines such as interleukin 6 (IL-6) [ 30 ], and steroid hormones such as 17β-estradiol (E2) [ 31 ]. The complexity of the molecular network and the variables in each cell system provoke a partial or intermediate EMT program, resulting in very diverse cellular phenotypes [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, high concentrations of E2 and a change in ERs expression levels have been detected in GBM biopsies, suggesting an essential role for these receptors in GBM pathology [ 44 , 45 , 46 , 47 , 48 ]. E2 through ER-α induces EMT in human GBM-derived cells [ 31 ]. EMT program activation by the E2 could vary in the microenvironment of GBM by interacting with the signaling pathways of other inducers of EMT, such as TGF-β.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the treatment with MPP, an antagonist of ERα, blocked the E2 and PPT effects. The agonist of ERβ, DNP, did not affect any processes [63].…”
Section: Gonadal Steroid Hormones In the Prevalence And Progression Omentioning
confidence: 82%
“…It was also determined that the mRNA expression of ERα and ERβ was higher in the mesenchymal glioblastoma subtype compared to the other three subtypes defined by Verhaak and cols [62]. Besides, using TCGA analysis, a higher expression of both ER subtypes was associated with a poor clinical outcome [63]. On the contrary, Jimenez and cols found that the lowest expression of ERα mRNA was associated with a bad prognosis [64].…”
Section: Gonadal Steroid Hormones In the Prevalence And Progression Omentioning
confidence: 96%
“…They found that in breast cancer cells no expressing ER, P4 induced the activation of cSrc through PR ( 22 ). In glioblastomas, estradiol increased cell growth, migration, invasion, and the epithelial–mesenchymal transition (EMT) through activation of ERα ( 57 , 58 ); therefore, we cannot dismiss the idea of the role of ERα in the PR-cSrc interaction.…”
Section: Discussionmentioning
confidence: 99%